Cryptonome beatrizae n. sp., from drifting wood in Western Mexico, with remarks on Pareurythoe Gustafson, 1930 (Annelida, Amphinomidae) - Tovar-Hernández, María Ana; González-Vallejo, Norma Emilia; Salazar-Vallejo, Sergio I. (Zootaxa, 2024)
Only five species of fireworms (Annelida: Amphinomidae) belonging to the genera Cryptonome Borda, Kudenov, Bienhold & Rouse, 2012, Linopherus de Quatrefages, 1866 and Pareurythoe Gustafson, 1930 have been reported as xylophilic. In this study, a new species of Cryptonome is described from driftwood found in the southern Gulf of California, including a short comment on other associated stowaways. Cryptonome is amended based on the presence of dorsal cirri being cirriform, smooth or pseudarticulate; Pareurythoe is restricted to specify the presence of caruncle sigmoid without lateral lobes and parapodial cirri smooth; and a key for identifying the species in Cryptonome is also included. The holotype of Hipponoe elongata Treadwell, 1931 is redescribed and newly combined in Cryptonome, whereas the holotype of Eurythoe spirocirrata Essenberg, 1917 previously regarded as Pareurythoe is returned to its original genus, Eurythoe Kinberg, 1857, and some of its morphological features are clarified.